Brazil : Financial Sector Assessment Program-Technical Note on Insurance Sector Regulation and Supervision. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2018)
The insurance sector has significant potential for expansion and to contribute to economic growth as an important part of the financial sector. While the insurance sector has grown at 10 percent annually over the last 5 years, on average, and remains profitable with high solvency ratios, the insurance penetration and density are lower than other emerging markets. Nevertheless, the insurance industry has the potential to reach to much higher levels of insurance penetration. A few large conglomerate groups-composed of banks, insurers and investments funds-dominate the insurance sector. Conglomerate groups account for more than 75 percent of the market share. Reflecting very conservative regulations imposed by the Banco Central do Brasil (BCB) and the Superintendency of Private Insurance (SUSEP), the interlinkages between banks and insurers are limited. Nevertheless, material contagion may occur through a reputational channel, adversely impacting the profitability of the linked business.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet